Investigation of high-temperature corrosion of graphite with SiC coating - Kenzhina, I.E.; Chikhray, Ye.V.; Shestakov, V.P.; Kulsartov, T.V.; Askerbekov, S.K.; Kalikulov, O.A.; Zholdybayev, T.K. (Recent Contributions to Physics, 2017)
The article describes the results of experiments on high-temperature corrosion of graphite with SiC coating. To ensure the safe operation of a high-temperature gas-cooled reactor (HTGR), it is necessary to investigate the behavior of fuel and graphite elements of its core in case of air and/or water ingress. Nowadays, the data on corrosion of numerous types of reactor graphites in oxygen, air and in water vapor is insufficient. In this work, experiments were conducted on high-temperature corrosion of IG-110 graphite (without and with SiC-coating) samples and the temperature dependences of kinetics of gas composition change in corrosion chamber with samples of graphite in temperature range from 750°C to 1400°C and at initial pressures of water vapor in the chamber 10-100 Pa were obatined. There is a significant difference in the rate of pressure change in corrosion chamber for various gases in experiments with graphite without coating at a fixed temperature. This fact states about different values of reaction rates and a complex mechanism of corrosion, which depends on processes having different constants. A qualitative analysis of the results of corrosion experiments was also carried out.